Differential Proliferation Effect of the Newly Synthesized Valine, Tyrosine and Tryptophan–Naphthoquinones in Immortal and Tumorigenic Cervical Cell Lines - Sergio Córdova-Rivas; Jorge Gustavo Araujo-Huitrado; Ernesto Rivera-Avalos; Ismailia L. Escalante-García; Sergio M. Durón-Torres; Yamilé López-Hernández; Hiram Hernández-López; Lluvia López; Denisse de Loera; Jesús Adrián López (Molecules, 2020)
We previously showed that microwave assisted synthesis is the best method for the synthesis of naphthoquinone amino acid and chloride-naphthoquinone amino acid derivatives by a complete evaluation of reaction conditions such as stoichiometry, bases, and pH influence. Following the same strategy, we synthesized chloride and non-chloride tyrosine, valine, and tryptophan-naphthoquinones achieving 85–95%, 80–92%, and 91–95% yields, respectively. The cyclic voltammetry profiles showed that both series of naphthoquinone amino acid derivatives mainly display one redox reaction process. Overall, chloride naphthoquinone amino acid derivatives exhibited redox potential values (E1/2) more positive than non-chloride compounds. The six newly synthesized compounds were tested in HPV positive and negative as well as in immortal and tumorigenic cell lines to observe the effects in different cellular context simulating precancerous and cancerous status. A dose-response was achieved to determine the IC50 of six newly synthesized compounds in SiHa (Tumorigenic and HPV16 positive), CaLo (Tumorigenic and HPV18 positive), C33-A (Tumorigenic and HPV negative) and HaCaT (Keratinocytes immortal HPV negative) cell lines. Non-chloride tryptophan-naphthoquinone (3c) and chloride tyrosine-naphthoquine (4a) effects were more potent in tumorigenic SiHa, CaLo, and C33-A cells with respect to non-tumorigenic HaCaT cells. Interestingly, there seems to be a differential effect in non-chloride and chloride naphthoquinone amino acid derivatives in tumorigenic versus non tumorigenic cells. Considering all naphthoquinone amino acid derivatives that our group synthesized, it seems that hydrophobic and aromatic amino acids have the greatest effect on cell proliferation inhibition. These results show promising compounds for cervical cancer treatment.